Psikoedukasi Pengelolaan Screen Time dan Komunikasi Asertif pada Remaja dalam Keluarga - Wigunawati, Eustalia; Lase, Formas Juitan; Jovani, Audra (Indonesian Journal for Social Responsibility, 2025)
While gadgets offer numerous benefits, such as ease of communication, information access, and enhanced creativity, their excessive use, especially among children and adolescents, leads to significant negative impacts. These include reduced book literacy, impaired concentration, eye problems, decreased physical activity, and social isolation. A lack of effective family communication exacerbates these issues, causing conflicts and potentially addictive behaviors related to gadgets. Observations at the Indonesian Western Protestant Church (GPIB) Menara Iman Jakarta indicate that children and adolescents within the congregation experience family communication problems due to high screen time. Statistical data further emphasize the urgency of intervention, with Indonesia ranking highest globally in screen time (averaging 5.7 hours/day) and Generation Z spending over 3 hours/day on social media. This Community Engagement (PkM) initiative utilized a psychoeducational approach implemented in two main stages: (1) an initial survey and engagement with church officials and congregants; and (2) the execution of the PkM program. The implementation mechanism involved interactive lectures by expert speakers and discussion and experience-sharing sessions to facilitate understanding and application of the material. The PkM activity engaged 12 adolescents from the GPIB Menara Iman Jakarta congregation, ranging from 10 to 17 years old. Pretests and posttests were conducted to measure participants' understanding. Based on a Wilcoxon signed-rank test analysis, significant results were obtained (W=0.000; p=0.002), indicating a substantial increase in participants' understanding regarding screen time management and assertive communication. This improvement demonstrates the effectiveness of the psychoeducational method in equipping adolescents with essential skills to build more functional and harmonious family communication.